4 Answers | Add Yours
Assume that the son's age = x
then the man age = 4 times as old ad his son = 4x
after 3 years:
the son age = x+3
the man age = 3 times as old as his son = 3(X+3)
but 3 years later, the man age was 4x so now his age is 4x+3
then 3(x+3) = 4x +3
==> 3x+9 = 4x +3
==> 6 = x
then the son age now = 6
and the man age = 4(6) = 24
after 3 years, the son will be 9
and the father will be 24+3 = 27 or 3(9)= 27
Right now, the man is 24 and his son is 6. Here is how you figure this out:
Let the man's age by M and the son's age be S.
Right now M = 4S
In three years
M + 3 = 3(S + 3)
So you put the 4S in to substitute for the M.
4S + 3 = 3(S + 3)
4S + 3 = 3S + 9
S = 6
If the son is 6, the father must be 24.
We can check this by adding three to both ages. Then, the son will be 9 and the father will be 27, which is three times 9.
Let's establish the followings:
a = the age of the son, now
b = the age of the father, now.
a+3 = the age of the son, after 3 years.
b+3 = the age of the father, after 3 years.
Now, the father's age is 4 times the son's age.
b = 4a (1)
After 3 years, the father's age will be:
b+3 = 3(a+3) (2)
We'll substitute the equation (1) into the equation (2).
4a+3 = 3a + 9
4a - 3a = 9-3
a = 6
b = 4*6
b = 24
The son is 6 years old and his father is 27 years old, now.
Let he sun's age now be x years
Then the father's age is by data = 4 times sun's age = 4x years.
After 3 years the ages of sun and father are: x+3 y and 4x+3y respectively.
By by data the father will be 3 times as old as son after 3 years. So : 4x+3 = 3 (x+3). Solving for x gives the age of the son. So
4x+3 = 3x+9 Or
4x-3x = 9-3 =6. Or
x =6. So the age of the sun now = x = 6 years. And the age of the father now = 4x = 4*6 = 24.
Tally after 3 years Son and father attain 9 years and 27 years . So the father' age will be 3 times sons age ,i.e 27 =3*9
We’ve answered 317,647 questions. We can answer yours, too.Ask a question